Vitamin D, Chronic Migraine, and Extracranial Pain: Is There a Link? Data From an Observational Study - Rebecchi, Valentina; Gallo, Daniela; Princiotta Cariddi, Lucia; Piantanida, Eliana; Tabaee Damavandi, Payam; Carimati, Federico; Gallazzi, Marco; Clemenzi, Alessandro; Banfi, Paola; Candeloro, Elisa; Tanda, Maria Laura; Mauri, Marco; et al. (Frontiers in Neurology, 2021)
Several studies focused on the role of vitamin D (vitD) in pain chronification. This study focused on vitD level and pain chronification and extension in headache disorders. Eighty patients with primary headache underwent neurological examination, laboratory exams, including serum calcifediol 25(OH)D, and headache features assessment along with three questionnaires investigating depression, anxiety, and allodynia. The 86.8% of the population had migraine (48% episodic and 52% chronic). The 44.1% of patients had extracranial pain, and 47.6% suffered from allodynia. A vitD deficit, namely a serum 25(OH)D level <20 ng/ml, was detectable in 46.1% of the patients, and it occurred more frequently (p = 0.009) in patients suffering from chronic migraine (CM)–medication overuse migraine (MOH) (62.9%) than in episodic migraine (EM, 25.7%) or tension-type headache (TTH, 11.4%). The occurrence of extracranial pain and allodynia was higher in the CM-MOH than in the EM and in the TTH groups but was not related to the co-occurrence of vitD deficiency (Fisher's exact test p = 0.11 and p = 0.32, respectively). Our findings show that 25(OH)D deficit is also related to chronic headache, probably because of vitD anti-inflammatory and tolerogenic properties, reinforcing the idea of a neuroinflammatory mechanism underpinning migraine chronification.